2014
DOI: 10.1098/rsif.2013.0921
|View full text |Cite
|
Sign up to set email alerts
|

Vision-based flight control in the hawkmothHyles lineata

Abstract: Vision is a key sensory modality for flying insects, playing an important role in guidance, navigation and control. Here, we use a virtual-reality flight simulator to measure the optomotor responses of the hawkmoth Hyles lineata, and use a published linear-time invariant model of the flight dynamics to interpret the function of the measured responses in flight stabilization and control. We recorded the forces and moments produced during oscillation of the visual field in roll, pitch and yaw, varying the tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 50 publications
(115 reference statements)
0
36
0
Order By: Relevance
“…Collett and Land, 1975;Lehrer and Srinivasan, 1992;Farina et al, 1995;Kern and Varju, 1998;Mronz and Lehmann, 2008;Theobald et al, 2009;Windsor et al, 2014), and suggested in hummingbirds and zebra finches (Srinivasan, 2001;Iwaniuk and Wylie, 2007;Eckmeier et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Collett and Land, 1975;Lehrer and Srinivasan, 1992;Farina et al, 1995;Kern and Varju, 1998;Mronz and Lehmann, 2008;Theobald et al, 2009;Windsor et al, 2014), and suggested in hummingbirds and zebra finches (Srinivasan, 2001;Iwaniuk and Wylie, 2007;Eckmeier et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the results on fruit flies reported here, PI control has also been identified in pitch control for hawkmoths (Cheng et al, 2011;Windsor et al, 2014). The anatomical similarities found across species suggest that pitch instability is an obstacle faced by many flapping insects (Ristroph et al, 2013;Sun, 2014;Sun et al, 2007); a natural question raised by these collective findings is whether PI control is a generic feature of pitch stabilization in flying insects.…”
Section: Linear Control Of Body Orientationmentioning
confidence: 74%
“…Thus, free-flight studies are necessary for a comprehensive understanding of pitch control. Significant analysis has been performed on freely flying insects executing voluntary maneuvers Ennos, 1989;Fry et al, 2003;Ristroph et al, 2011Ristroph et al, , 2009 or responding to visual stimuli (Cheng et al, 2011;Muijres et al, 2014;Tammero and Dickinson, 2002;Windsor et al, 2014), but the general challenge of systematically inducing mechanical perturbations on untethered insects has traditionally been a barrier to the study of stabilization reflexes. Some notable exceptions to this include methods of mechanical perturbation using air-flow vortices (Combes and Dudley, 2009;Ortega-Jimenez et al, 2013;Ravi et al, 2013) or gusts of wind (Vance et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Vision is critical to navigation [189], landing [205], chasing prey, avoiding obstacles, as well as stabilizing flight [206]. Unlike larger animals that mostly use stereopsis and object recognition to navigate and estimate distance, tiny insects rely on compound eyes.…”
Section: (B) Visual Sensingmentioning
confidence: 99%